SETTING OF DEVELOPED COUNTRY IN DRAMA SCRIPT “NYAYIAN RIMBAYANA” (A Study of Roland Barthes’ Semiotics with Myth of Liberal Capitalism) - DEDEN NOVAN SETIAWAN NUGRAHA (Lembaga Penelitian Universitas Pasundan, 2017)
The analysis of this research basically concerns issue of setting of developed country which is depicted through the sign systems found in the drama script “Nyayian Rimbayana”. Principally, the research is a descriptive qualitative research with Roland Barthes’s semiotics as the main tool to examine the data. The sign systems detected are interpreted in two orders of significations (language level and myth level). Observed based on the myth of liberal capitalism, the setting of developed country illustrated through the sign systems are specifically in principles of modernity of infrastructure (infrastructure appearance); diversity of social class, capital force (social class); mercantilism, non-intervention of government, policies of encouragement, the disregard of domestic policies, and non-inward-looking development policies (leader role); and market force, free market system, openness of country’s economies, profit motive, private ownership property, and no legal limit on the accumulation of property (industrial prototype). Key words: Drama, semiotics, developed country, liberal capitalism.